Innovative Hybrid War Strategy Optimization with Incremental Conductance for Maximum Power Point Tracking in Partially Shaded Photovoltaic Systems - Khaterchi Hechmi; Regaya Chiheb Ben; Jeridi Ahmed; Zaafouri Abderrahmen (Power Electronics and Drives)
This paper introduces a novel maximum power point tracking (MPPT) controller for photovoltaic (PV) systems that leverages the strengths of both metaheuristic and heuristic methods. Classical MPPT algorithms, such as incremental conductance (IC) and perturb and observe (P&O), are widely used but often struggle with instability, oscillations near the steady state, and slow convergence, particularly under fluctuating weather conditions such as static partial shading conditions (PSCs). To address these challenges, we propose a hybrid MPPT approach that combines the war strategy optimization (WSO) algorithm with the IC method, termed war strategy optimization-incremental conductance (WSO-IC). The performance of the WSO-IC algorithm is rigorously compared against traditional IC, P&O, and standalone WSO techniques. Simulation results validate that the WSO-IC approach provides superior MPPT with faster convergence and high efficiency. The results obtained in SIMULINK demonstrate that the proposed method can achieve efficiencies exceeding 99%, even under static partial shading conditions.